1989
DOI: 10.3354/dao007039
|View full text |Cite
|
Sign up to set email alerts
|

The membranous labyrinth in baculovirus-infected crustacean cells: possible roles in viral reproduction

Abstract: The origins and morphogenesis of the membranous labyrinth (ML) in Baculov~rus penaei (BP) infected cells of penaeid shrimps (Crustacea:Decapoda) are described. The \IL is usually a highly ordered, complex system of membranes arranged as a labyrinth or in concentric form in the cytoplasm near or against the nuclear envelope. The ML originates from dilated Golgi and endoplasmic reticulum vesicles, and from the outer nuclear envelope. It grows apparently from proliferation of the cellular membranes of these syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Infected cells were seen to contain large numbers of mitochondria, showed dilation of the outer nuclear membrane, and often developed an intricate membranous system reminiscent of the membranous labyrinth system described by Couch (1989) in Baculovirus penaei (BP)-infected penaeid shrimps. In the BP model, it is suggested that the labyrinth system may originate from 3 sources (the outer nuclear membrane, the Golgi and the endoplasmic reticulum) and that it can form concentric membrane masses or a highly organized labyrinthian structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infected cells were seen to contain large numbers of mitochondria, showed dilation of the outer nuclear membrane, and often developed an intricate membranous system reminiscent of the membranous labyrinth system described by Couch (1989) in Baculovirus penaei (BP)-infected penaeid shrimps. In the BP model, it is suggested that the labyrinth system may originate from 3 sources (the outer nuclear membrane, the Golgi and the endoplasmic reticulum) and that it can form concentric membrane masses or a highly organized labyrinthian structure.…”
Section: Discussionmentioning
confidence: 99%
“…In the BP model, it is suggested that the labyrinth system may originate from 3 sources (the outer nuclear membrane, the Golgi and the endoplasmic reticulum) and that it can form concentric membrane masses or a highly organized labyrinthian structure. The role of the labyrinth is to provide structural precursors to the developing virions, and in the case of BP, for the polyhedrin-rich occlusion body (Couch 1989). Modification of cytoplasmic membrane structures has also been noted for other baculovirus infections of shrimps (Lightner et al 1983) and for several viruses from other groups (Couch 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vogt (1992) observed a proliferati.on of smooth endoplasmic reticulum (ER) into concentric membrane whorls indicative of lipid catabolism in HP cells of P monodon infected with the baculovirus MBV He reported that HP cells in the advanced stages of infection lacked lipid reserves. Couch (1989) observed the formation of a membranous labyrinth (ML) from ER vesicles in BP-infected P. duorarum during the early stages of viral infection. He observed that the ML is closely associated with viral repliHours Post-Exoosure .…”
Section: Discussionmentioning
confidence: 95%
“…Histopathologic damage 'E-mail. sywang@whale st usm edu occurs when hepatopancreatic and midgut epithelia1 cells are destroyed during occlusion body formation and subsequent eruption from host cells (Couch 1981(Couch , 1989.…”
Section: Introductionmentioning
confidence: 99%